The Managers Pocket Guide to Team Sponsorship. - Pope, Sarah (Managers Pocket Guide Series., 1998)
Are you responsible for starting new teams, providing direction, allocating resources, removing roadblocks, and serving as an all-around champion for high-performance work teams? This practical, step-by-step guide is for you! Not only does this pocket reference emphasize the importance of turning slogans and talk into action, it tells how to do it. You'll get helpful guidelines for turning the principles of team management into day-to-day actions. Each chapter begins with a set of questions that the sponsor must ask before starting any team. The answers to these questions provide the keys to w.